Weight loss and adipose (fat) tissue oxidation in fitness/La pérdida de peso y la oxidación del tejido adiposo (grasa) en el fitness - Darío Paúl Guamán Sanguña (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: Fitness is aimed at improving physical condition and general health, where weight control and loss are basic guidelines to improve body balance, enhancing aerobic resistance. To be informed about the level of knowledge of the national specialists will delimit the scope and limitations to be developed in a future intervention program. Objective: To validate the level of knowledge of a group of national specialists on weight loss through the oxidation of adipose tissue (fat) in fitness. Materials and methods: The research is descriptive-explanatory with correlational reinforcement, selected under an intentional non-probabilistic sampling of 32 national fitness specialists through two inclusion criteria, for which they will qualify eight theoretical indicators that will serve as a methodological basis to design a future, a sustainable model of fitness training. Results: The individualization, the complementary alternatives and the anaerobic method obtained the lowest average scores (1.81 points, 2.31 points and 2.53 points respectively) in their level of importance, while affordability and sustainability a medium level (3.19 points; 3.34 points) and the indicators systematic control, level of importance and the aerobic method the ones with the best score respectively (4.13 points, 4.56 points and 4.75 points). The indicators analyzed show different levels of importance. Conclusions: It is recommended to train national fitness professionals on the real levels of importance of each indicator, emphasizing the integration of each training component, including the principles studied, anaerobic training as a complement to the aerobic intervention process and complementary alternatives.